Factors Associated With Carpal Tunnel Syndrome (CTS) Complaints in Betel Nut Split and Sort Workers In Cv. Indokara - Budi Aswin; Nadia Olimvia; La Ode Reskiaddin (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: The work of splitting and sorting areca nuts is done manually with repetitive movements for a long duration. Inappropriate work postures that are not ergonomic and repetitive movements for a long time are one of the risk factors that can trigger Carpal Tunnel Syndrome (CTS). Purpose: This study aims to identify factors that contribute to the emergence of CTS complaints in areca nut splitting and sorting workers at CV. Indokara in 2024. Research methods: This study used an analytical observational design with a quantitative approach and a cross-sectional plan. All workers in the areca nut splitting and sorting section at CV. Indokara became the study population, with a sample size of 38 people obtained through the total sampling technique. Results and discussion: The prevalence rate of CTS complaints found in workers at CV. Indokaraa reached 55.3%. The results of statistical analysis showed that there was a relationship between age (p = 0.031), length of service (p = 0.011), work posture (p = 0.031) and repetitive movements (p = 0.029) with CTS complaints. However, there was no correlation between nutritional status (p = 1,000) and CTS complaints. Conclusion: Age, length of service, work posture, and repetitive movements are related to CTS complaints in areca nut splitting and sorting workers at CV. Indokara in 2024. Therefore, workers are advised to use their break time to stretch their hands regularly. In addition, a policy regarding routine exercise once a week can be implemented and create a posture regarding stretching movements that need to be done by workers.